Increased choroidal thickness in patient with high-altitude retinopathy - Hirukawa-Nakayama, Kyoko (Medknow Publications & Media Pvt Ltd, 2014)
We report a case of high-altitude retinopathy with increased choroidal thickness detected by spectral-domain optical coherence tomography (SD-OCT). A 36-year-old Japanese man developed an acute vision decrease in his left eye after he had trekked at an altitude of 4600 m in Tibet for 1 week. His visual acuity was 20/20 OD and 20/200 OS with refractive errors of − 0.25 diopters (D) OD and − 0.50 D OS 3 weeks after the onset of the visual decrease. Funduscopic examinations revealed multiple intraretinal hemorrhages bilaterally and a macular hemorrhage in the left eye. SD-OCT showed that the thickness of choroidal layer at the fovea was 530 μm OD and 490 μm OS which is thicker than that in normal subjects of approximately 300 μm. We suggest that the increase in the retinal blood flow under hypoxic conditions may be associated with an increase in the choroidal blood flow resulting in an increase in choroidal thickness.